Gravity for FDI - Jörn Kleinert; Farid Toubal (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2005)
We derive gravity equations from three different general equilibrium models incorporating multinational firms. We show that gravity equations are particularly adapted to the analysis of foreign affiliates' activities of multinational firms. However, the different theoretical models lead to different specifications and interpretations of the empirical results. This is particularly the case considering gravity equations derived from factor proportion models compared to those derived from proximity concentration theories.
Keywords: C21; F12; F23; 330; Gravity equation; multinational firms; heterogeneity; Direktinvestition; Multinationales Unternehmen; Gravitationsmodell; Faktorproportionentheorem; Allgemeines Gleichgewicht; Theorie